APLIKASI GAME EDUKASI AKSARA MATCHING BERBASIS ANDROID MENGGUNAKAN UNITY3D - Rian Oseady Prahastito; Didik Kurniawan; Astria Hijriani (Jurnal Komputasi, 2016)
The development of educational game is motivated by low interest and desire of people to learn Aksara Lampung, therefore, in this case is required a learning system which is attractive and pleasant so it can attract people to keep follow the development of existing technologies, one of which is a learning system by using media of educational game. This research used eXtreme Programming (EX) method and was designed by using Unified Modeling Language (UML). This application tested by using Black Box Testing method with the approach of Equivalence Partitioning (EP) and the calculation of Likert Scale. On the other side, based on the results obtained from the questionnaire, this application is user friendly application (with an average value of 77% / Excellent).